PERAN SESAR TERHADAP KARAKTER DAN ARAH ALIRAN AIRTANAH PADA ENDAPAN VOLKANIK DI LERENG TENGGARA G. GEDE, KABUPATEN CIANJUR, JAWABARAT - -, Ismawan T.; -, Yudi Rahayudin; -, Boy Yoseph CSSSA; -, Bombom Rahmat Suganda; -, Nursiyam Barkah (Fakultas Teknik Geologi Universitas Padjadjaran, 2013)
Volcano as high morphology feature acts as a good water catchment and recharge area. This area also has a volcanic deposition characteristic that changes within a near range, and usually has complex geological structures that effects the groundwater systems. The aim of this study is to identity the role of faults toward groundwater conditions, determine facies and shallow groundwater flow based on the water table. The study area is in a volcanic deposition aquifer system that is composed of lapilli tuff, volcanic breccias, and sand. The occurance of several springs with groundwater conditions are controlled by faults and fractures. Physical characteristics of the water comprises, EC=104μS/cm -490 μS/cm, TDS = 49 mg/L- 240 mg/L, pH 4,2 – 8,6, Temperature 20,4°C – 26°C, debit 0,05 L/sec up to 100 L/sec. Chemical facies of the water is divided into three types: Ca, HCO3, Ca, Mg HCO3 and Mg, Ca HCO3.The direction of the shallow groundwater flow generally follows the topographics features with a direction northwest-southeast.